2013
DOI: 10.1111/jan.12077
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of alternating pressure mattresses and overlays for prevention of pressure ulcers in ventilated intensive care patients: a quasi‐experimental study

Abstract: This quasi-experiment study that alternative pressure air mattresses were more effective than alternating pressure air overlays in preventing pressure ulcers in mechanically ventilated critical care patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(64 citation statements)
references
References 31 publications
0
63
0
1
Order By: Relevance
“…Preventive interventions include offloading pressure via turning, repositioning of pressure points, and use of pressure-relieving devices. The results of previous research support the timely placement of at-risk patients on low air loss and pressure-relieving or pressure-redistribution mattresses [23][24][25][26][27][28] or air-fluidized beds. 29 Low air loss mattresses help control the skin microclimate to reduce skin moisture and temperature, thereby reducing injury of tissue surfaces that interface with the mattress.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Preventive interventions include offloading pressure via turning, repositioning of pressure points, and use of pressure-relieving devices. The results of previous research support the timely placement of at-risk patients on low air loss and pressure-relieving or pressure-redistribution mattresses [23][24][25][26][27][28] or air-fluidized beds. 29 Low air loss mattresses help control the skin microclimate to reduce skin moisture and temperature, thereby reducing injury of tissue surfaces that interface with the mattress.…”
Section: Discussionmentioning
confidence: 59%
“…970 (5873) 59 (63) 21 (23) 100 (92) 6 (23) 92 (84) 7 (68) 88 (27) 122 (37) 128 (39) 30 (9) 93 (86) 10 (3) 10 (3) 10 (3) 2.8 (0.7)…”
Section: Methodsunclassified
“…31,32 Pressure-relieving mattresses can prevent pressure ulcers in ICU patients. 33,34 Despite the concern for pressure ulcer risk with HOB elevation greater than 30º, the current study demonstrated the safety of HOB elevation greater than 30º for 12 to 24 hours with pressure ulcer prevention measures.…”
Section: Discussionmentioning
confidence: 99%
“…, Manzano et al . ). These studies identified predictive factors such as non‐blanchable erythema, existing wounds, diabetes, low haemoglobin level on admission or before surgery (Nixon et al .…”
Section: Introductionmentioning
confidence: 97%